Fabrication and optimization of buccal film comprising rizatriptan benzoate loaded solid lipid nanoparticles for improved ex vivo permeation - Salve, Pramod; Bali, Nikhil (Journal of Drug Delivery and Therapeutics, 2019)
The objective of the present study was to fabricate and optimize mucoadhesive buccal film encloses rizatriptan benzoate (RBZ) loaded solid lipid nanoparticles (SLNs) for improved ex-vivo permeation. RBZ loaded SLNs were formulated by hot high pressure homogenization method. SLNs were characterized for size, zeta potential and scanning electron microscopy (SEM). The RBZ SLNs comprising mucoadhesive buccal film were fabricated using dependent variables in different concentration of Eudragit RS100 and HPMC K4M by using solvent evaporation method. The formulations were experimentally optimized using two factors, three level statistical design approach. The formulated buccal film comprising RBZ SLNs evaluated for mucoadhesive strength, swelling index, drug release and ex vivo permeation. The optimized formulation of RBZ SLNs showed particle size, polydispersity index, zeta potential and entrapment efficiency i.e. 228 nm, 0.22±0.02, -14mV, 81.78% respectively. Optimized mucoadhesive buccal film formulation followed Korsmeyer-Peppas drug release kinetic model with non-Fickian diffusion mechanism. Flux, lag time, permeability values in ex vivo permeation of RBZ from SLNs loaded film were found to be 0.071µg/cm2.h, 60 min., 0.014 respectively. The flux and permeability values were increased and lag time for permeation was decreased in ex vivo permeation studies of RBZ SLNs buccal film as compared to RBZ film. The results of the in vitro and ex vivo permeation study advocate the mucoadhesive film comprising RBZ SLNs is encouraging approach for drug delivery to brain targeting diseases.Keywords: Solid Lipid nanoparticles; Rizatriptan benzoate; Buccal film; Bioavailability.